Punding Behavior as a Red Flag for Dementia in a Patient With Depression: Case Report - Pouchon, Arnaud; Dondé, Clément; Polosan, Mircea (Frontiers in Psychiatry, 2021)
Punding is defined as a stereotypic, complex, repetitive and non-goal-oriented activity. This behavior has been observed in Parkinson’s disease and chronic amphetamine users. However, in general, punding behavior is largely under-diagnosed. Here, we describe a rare case of a 53-year-old woman showing punding behavior during major depressive disorder with atypical clinical features suggestive of a frontal syndrome. Neuropsychological evaluations mainly reported deficits in executive functioning. Brain MRI and lumbar puncture were normal. Brain perfusion SPECT showed hypoperfusion predominating in the right frontal and parietooccipital lobes, and a slight hypoperfusion in subthalamic nucleus including the posterior area of right striatum. We diagnosed this case as a frontotemporal dementia. Punding behavior could be a red flag for dementia in patients with major depressive disorder.